Musician as an ideologue - Dele Maxwell Ugwanyi; Lucy Chioma Ezekeke (ESUT JOURNAL OF SOCIAL SCIENCES, 2022)
Music has been used to project social and spiritual interactions irrespective of cultural and socio-political worldview of the people. Its entertainment value seems to have taken precedence over socio-political and spiritual utilities. Musicians are regarded as agents of social awareness and reformation that expose and correct the incidences in the society. Without strong ideological leaning it will be pretty difficult for any musician to impact his society positively apart from the entertainment values. This study is undertaken to take a look at two prominent musicians that influenced their societies as a result of their strong ideological persuasion. Their music has remained very relevant today even long after they exited the stage and the world. They were not only ideologically grounded, they were equally visionary and their music serves multiple purposes in our contemporary world. The study selected Bob Marley and Fela Anikulapo-Kuti whose music did not only provide entertainment values but supplied us with a standard with which we assess our social-cultural and spiritual interactions. The study submits that without strong ideological foundations the two musicians would have possibly died with their music. Today their music has remained evergreen and indelible because of the strong ideology that heralded and influenced their songs. The study therefore concludes that music should not be for music sake or mainly for entertainment purposes but for socio-cultural, political and spiritual interactions which cannot be achieved without deep ideological foundation.